Three-dimensional hedgehog-like ZnO/SnO2 hierarchical heterostructure for high performance self-powered ultraviolet photodetector. (July 2022) - Rong, Ping; Mao, Mouwen; Gao, Shiyong; Lu, Huiqing; Ren, Shuai; Li, Lin; Xu, Zhikun; Ling, Duoduo; Han, Mingrui; Wang, Jinzhong
Abstract: A novel hedgehog-like ZnO/SnO2 hierarchical heterostructures composing of one-dimensional ZnO nanorods (NRs) and three-dimensional SnO2 octahedron nano-blocks (ONBs) have been successfully prepared on ITO substrate through a simple solution method. The results show that ZnO NRs are uniformly and densely distributed perpendicular to the surface of the SnO2 ONB. The as-prepared ZnO NRs/SnO2 ONB (Z/S) hierarchical heterostructure is applied to assemble ultraviolet photodetector (UVPD). Under UV light illumination, it can obviously find that the Z/S UVPD can work at zero bias voltage and exhibits a remarkable stability and repeatability. In addition, the Z/S UVPD displays excellent characteristics over that based on SnO2 ONBs, in particular a relatively high photoresponsivity, a strong photocurrent density of 0.94 mA cm −2, together with a high on/off ratio of 5362. Moreover, the possible mechanisms for growth and UV detection on the hedgehog-like Z/S hierarchical heterostructure have been discussed.